PENGARUH IMPLEMENTASI TOTAL1QUALITY MANAJEMEN TERHADAP KINERJA1OPERASIONAL PADA CV AL-MAIDAH - Aviro, Iftitah Noranza; Fatimah, Feti; Nursaidah, Nursaidah (Relawan Jurnal Indonesia, 2023)
This study was conducted at CV Al-Maidah in Jember, aiming to assess the impact of variables such as Customer Satisfaction (X1), Employee Empowerment (X2),1Continuous Quality Improvement (X3), and1Management Based on Facts (X4) on Operational Performance (Y). Data collection took place in December 2023, involving 82 employees of CV Al-Maidah through a saturated sample method. The research adopts a quantitative approach with an explanatory research design, utilizing data from surveys, observations, and secondary sources related to CV Al-Maidah. The analysis of the data reveals that all four independent variables significantly influence Operational Performance. Customer Satisfaction, Employee1Empowerment, and Continuous Quality Improvement exhibit positive effects, while Fact-Based Management demonstrates a negative impact. Classical assumption tests affirm that the data is normally distributed and free from multicollinearity1and1heteroscedasticity. Hypothesis testing and the coefficient of determination indicate that, collectively, the independent variables explain 78% of the variance observed in Operational Performance.